Molecular and hematological studies in a cohort of beta zero South East Asia deletion (β°-thal SEA) from Malaysian perspective - Yasin, Norafiza Mohd; Abdul Hamid, Faidatul Syazlin; Hassan, Syahzuwan; Sudin, Aziee; Yassim, Haiyuni; Mohd Sahid, Ermi Neiza; Mat Yusoff, Yuslina; Esa, Ezalia; Saleem, Mohamed (Frontiers in Pediatrics, 2022)
Abstract We report the haematological parameters and molecular characterization of beta zero (β°) South East Asia (SEA) deletion in the HBB gene cluster with unusually high levels of Hb F compared to a classical heterozygous beta zero (β°)-thalassaemia. Methods Retrospective study on 17 cases of (β°) South East Asia (SEA) deletion from 2016 to 2019 referred to Institute for Medical Research were conducted. The clinical information and haematological profiles were evaluated. The mutation was analyzed, and the results were compared with other β°-thalassaemia groups. For HBB gene genotyping, all the cases were subjected for multiplex gap-PCR, 5 cases were subjected for HBB gene sequencing for exclusion of compound heterozygous with other beta variants. Co-inheritance of α-thalassaemia were determined using multiplex gap-PCR and multiplex ARMS-PCR. Results Seventeen cases were positive for β°-thal SEA deletion. Fifteen cases were heterozygous and two were compound heterozygous for β°-thal SEA deletion. The results were compared with 182 cases of various heterozygous β° deletions and mutations. The mean Hb for heterozygous β°-thal SEA deletion (13.44 ± 1.45 g/dl) was normal and significantly higher than heterozygous IVS 1-1 and Codon 41/42 (post hoc test, p < 0.05). The medians for the MCV and MCH of β°-thal SEA deletion were significantly higher than for all heterozygote β°-thalassaemia traits (Mann Whitney test, p < 0.05). Patients with β°-thal SEA deletion had elevated levels of Hb A2 consistent with β-thalassaemia traits, with Hb F levels consistent with HPFH or δβ-thalassaemia carriers. The median for Hb A2 was 4.00 + 1.00%, similar to that observed in other β°-thalassaemia groups except for IVS 1-1 mutation (median 5.30 + 0.45%) and β°-Filipino (∼45 kb deletion) deletion (median 6.00 + 0.58). Interestingly, we found that Hb F levels for β°-thal SEA deletion were statistically higher than other β°-thalassaemia mutations (median 19.00 + 5.50%, p < 0.05), except for the β°-thal 3.5 kb deletion group. Conclusion We conclude that β°-thal SEA deletion has a unique haematological parameters of beta zero thalassaemia trait. We affirm to classifying this deletion as SEA-HPFH based on previous studies considering the phenotype features rather than the molecular defect of β°-thal SEA deletion, as this will make it easier to offer genetic counselling to affected individuals.